THE DIFFERENCES OF COGNITIVE STYLE FIELDS-INDEPENDENT AND DEPENDENT ON STUDENTS' MATHEMATICAL PROBLEM SOLVING ABILITIES - Hasbullah Hasbullah; Supardi Uki Sajiman (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2020)
The study aims to determine the differences in field-independent cognitive styles with a dependent on students' mathematical problem solving abilities. This researcher uses a quantitative approach with a correlational survey method with factual exposure research types. The study population was the seventh grade students of Madrasah Tsanawiyah in Lombok Timur, amounting to 680. The sampling used was simple random sampling technique. The sampling technique uses percentage techniques. From a population of 680 people taken 10%, so the number of samples in this study was 68 people. The hypothesis analysis test used the t test with SPSS 22. The results showed that there was a difference between students' mathematical problem solving abilities in the group of students who had a field independent cognitive style and a group of students who had a field dependent cognitive style. the principal in recruiting students to enter the Madrasah Tsnawiyah, not only the value of the results of the National Primary School exam but rather the grouping of students based on independent and field dependent cognitive field styles